Effect of Transparency Initiatives on Public Trust in Government in Kenya - Wanjala, Dennis (Journal of Public Policy and Administration, 2024)
Purpose: To aim of the study was to analyze the effect of transparency initiatives on public trust in government in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Transparency initiatives in Kenya have shown a positive impact on public trust in government. Efforts such as open access to government information, transparent budgeting processes, and public participation in decision-making have increased accountability and reduced corruption. These initiatives have led to greater citizen engagement and trust, as the public perceives the government to be more accountable and responsive to their needs. However, challenges remain in fully implementing these initiatives, and inconsistencies in transparency efforts can still undermine public trust. Unique Contribution to Theory, Practice and Policy: Social exchange theory, institutional theory & information processing theory may be used to anchor future studies on the effect of transparency initiatives on public trust in government in Kenya. Continuously improve online transparency portals by enhancing user interfaces, ensuring data accuracy, and expanding the scope of information available. Develop sector-specific transparency policies tailored to the unique needs of different governmental sectors (e.g., healthcare, education). This approach ensures that transparency initiatives address sector-specific challenges and enhance sector-specific public trust. Invest in training programs for public officials on transparency practices and the effective use of transparency tools.